Male Peacocks as a Source of Ideas for Creating the Gandrung Liwung Dance - Deti Lindiana; Trianti Nugraheni (Journal of Dance and Dance Education Studies, 2025)
Gandrung Liwung Dance was created as a new creative dance inspired by the behavior and beauty of the male peacock. This dance combines elegance and visual beauty displayed through dance movements and costumes that have new innovations resulting from the creativity of the dance creator. This study aims to identify the creative process of creating the Gandrung Liwung Dance inspired by the male peacock as a source of inspiration for new creative dance. The research method used is the descriptive qualitative approach analysis method. Data collection techniques through observation, interviews and documentation. Participants in this study were Riyana Rosilawati who is the choreographer or creator of the Gandrung Liwung Dance. The data collected were then analyzed through a preliminary study stage before the field research process and field data analysis. This study reveals an idea or concept in the process of creating the Gandrung Liwung Dance, starting with observing the behavior of the peacock and then developed to create a concept for creating works through the development of musical and artistic accompaniment consisting of make-up and costumes. Then, the process of forming the choreography is divided into three stages, namely exploration, improvisation, and composition and movement in. Gandrung Liwung Dance imitates the behavior of male peacocks. Overall, the new creative dance was created to convey the real behavior of male peacocks when they are about to be in heat. This research is implied as a new report in developing new creative dance creations for practitioners and dance art researchers.